Hyperbole: A Pragmatic View - Saleem, Zerin; Moussa, Abdelwahab (Humanities Journal of University of Zakho, 2021)
Hyperbole is an important subject of pragmatics and has a major role in both spoken and written language. The present research aims mainly to find out how Hyperbole occurs and define it in the areas of pragmatics within the framework of Kurdish language speakers in the center of the Dohuk region and to analyze the examples according to the descriptive-analytical approach. The main conclusion of research is that Hyperbole is related to pragmatics and is reflected in all its fields. The research generally consists of two chapters. The first chapter is entitled (The concept and definition of Hyperbole) and the second chapter is devoted to Hyperbole the levels of meaning, especially the pragmatic ones.